Immobilization of Urease on DEAE-Cellulose Strips for One Step Urea Detection - Kayastha, Arvind M. (Annals of the National Academy of Medical Sciences (India), 2019)
Urease isolated from pigeonpeas was immobilized on 1 cm × 6 cm diethylaminoethyl (DEAE)-cellulose strips. The optimum immobilization (55% activity) was observed at 4°C, with a protein concentration of 1 mg per strip at pH 6.5. Immobilized strips stored at 4°C showed an increased shelf-life and there was no leaching of enzyme from the immobilized strips for 6 months. Enzyme could be eluted on application of 0.2 M KCl in buffer, which showed that the binding of the enzyme was tight on DEAE-cellulose strips. These strips when used along with dye, phenol red (coimmobilized) gave different shades from light yellow to dark magenta depending upon the concentration of urea. The ease of immobilization of urease on DEAE-cellulose strips and easy availability of pigeonpeas urease described in the present study makes it a suitable product for potential applications in urea diagnostics.
Keywords: diethylaminoethyl-cellulose paper strips; urease; urea; immobilization; analytical application